Inovasi Pelayanan Pendidikan (Studi Kasus: Program Sumbangan Pembinaan Pendidikan (SPP) Gratis Bagi Mahasiswa Kabupaten Pangkep - Ulfa, Maria; Mahsyar, Abdul; Ma'ruf, Adnan (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2020)
This study to determine the characteristics of Educational Services Innovation (Case Study: Free Educational Assistance Donation Program For Pangkep Regency Students).The number of informants in this study was 14 people. This study used a qualitative approach and the type of descriptive research and case studies. Data collection techniques used observation, interviews and documentation. The result of this study showed that the characteristics of educational service innovation (case study: free educational assistance donation program for pangkep regency students) had fulfilled the five characteristics of innovation according to Roger,  namely relative advantage, compability, complexity, triability,and observability. But the implementation still required quite a long time or  was not yet effective